The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/bcj.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic significance of karyotypic subgroups in older patients with acute myeloid leukemia: the Swedish population-based experience

Abstract: The Swedish population-based acute myeloid leukemia registry contains data from 3251 patients (excluding acute promyelocytic leukemia) diagnosed between 1997 and 2006. Informative cytogenetic data from 1893 patients were retrospectively added, including 1054 patients aged between 60 and 79 years. Clonal abnormalities were found in 57% of the informative karyotypes. Karyotypic patterns differed by age: t(8;21), inv(16) and t(11q23) were more common in younger patients, whereas loss of 5q, 7q and 17p, monosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 34 publications
8
47
1
Order By: Relevance
“…We observed a similar number of cases of AML inv(16)(p13.1q22)/t(16; 16)(p13.1;q22) and AML t(8; 21)(q22;q22) (388 and 495 cases, respectively, among 16,328). These results are consistent with those of other groups who studied predominantly white populations in Sweden and Australia [24-26]. In contrast, studies of Asian populations found 3–7 times more cases of AML t(8; 21)(q22;q22) than of AML inv(16)(p13.1q22)/t(16; 16)(p13.1;q22) [25-27].…”
Section: Discussionsupporting
confidence: 91%
“…We observed a similar number of cases of AML inv(16)(p13.1q22)/t(16; 16)(p13.1;q22) and AML t(8; 21)(q22;q22) (388 and 495 cases, respectively, among 16,328). These results are consistent with those of other groups who studied predominantly white populations in Sweden and Australia [24-26]. In contrast, studies of Asian populations found 3–7 times more cases of AML t(8; 21)(q22;q22) than of AML inv(16)(p13.1q22)/t(16; 16)(p13.1;q22) [25-27].…”
Section: Discussionsupporting
confidence: 91%
“…These results demonstrate that the MK is a major independent very poor prognosis factor in elderly AML. During the past few years, several large studies have been conducted to analyze the prognostic impact of the MK on the outcome of AML (summarized in Table 1), confirming the previously reported findings 1,5,913,1724. Moreover, a recent report demonstrated that the combination of CK (defined in this study as unrelated chromosomal abnormalities ≥4) and the MK missed the least number of patients with unfavorable prognosis 18…”
Section: Introductionsupporting
confidence: 88%
“…In the present study, the median age of adult AML was lower (38 years) in comparison to Western population (40 -45 years) and other Asian population [6] [8] [9] [31]- [34] [41]. In adult AML, the incidence of t(8;21) was higher (15%) than that of Western population (6% -8%) and comparable to that in Chinese (8% -15%) and Japanese (16%) populations [3] [46].…”
Section: Discussionmentioning
confidence: 60%